"All Our Children May be Taught of God": Sunday Schools and the Roles of Childhood and Youth in Creating Evangelical Benevolence. Issue 4 (19th February 2019) - Leal, K. Elise
Abstract : Merging religious history with childhood studies, this article analyzes the rise of the Sunday school movement to show how concepts of childhood, and young people themselves, helped shape early American religious culture. Religious disestablishment, republican concerns about virtue, and romanticized reconstructions of childhood led to a heightened focus on young people within late eighteenth- and early nineteenth-century Protestant reform movements. The resulting dissemination of Sunday schools across the country established physical and imagined communities of faith dedicated exclusively to young people. They also fostered unprecedented levels of youth religious leadership by allowing adolescents to serve as teachers, challenging inherited patterns of social and cultural authority. Sunday schools thereby became transformative and transactional spaces where young people could both shape and be shaped by the growing Protestant community. This article describes this synergistic relationship between childhood, youth, and Protestant benevolence by examining the two related educational models that emerged within the Sunday school movement in the early national period. The first, exemplified by republican-humanitarian Sunday schools founded in the late eighteenth century, emphasized literacy instruction for the purpose of creating a virtuous citizenry. The second model also aspired to create virtuous citizens, but it envisioned using Sunday schools primarily to evangelize and sanctify the nation. The increasing emphasis on evangelism produced an even more significant structural shift: the transformation of Sunday schools into child-centric institutions that facilitated youth religious leadership. This in turn helped inaugurate a period within American Christianity when institutions and ministries were designed specifically for children on mass scale, permanently altering the religious landscape and redistributing spiritual authority to more marginalized groups, including young people themselves. By revealing how age became an increasingly crucial factor in determining the shape and substance of religious experiences, this article demonstrates that ideals and anxieties about childhood helped create volunteerism, which in turn reshaped the structure of American Protestantism while simultaneously contributing to the formation of a broader child-centric culture that persists in the modern day.